Especulação do solo urbano em Marechal Cândido Rondon (1980-2008): uma análise sobre as relações políticas e empresariais - Bade, Cristiane (2011)
The study is to analyze the formation of urban space in the city of Marechal Cândido Rondon, during the period 1980 to 2008, questioning the practice of urban land speculation. To analyze the problem proposed, organized the essay into three chapters. In the first chapter we seek to understand the formation of political groups and real estate in the city, for we did a historical analysis of the colonization period addressed by the company Maripá. In the second chapter we emphasize urban land speculation, analyzing the political and business leaders. In this chapter, we analyze also the speculation in certain areas that remain "empty" in the city and in some cases we present photographs of these places. In the third chapter we study the urban land speculation in areas surrounding the Ecological Park Rodolfo Rieger, a public invest-ment projected for businessmen and politicians (investors). The sources of the study were oral sources, recording sessions of the City Hall (Minutes), news sources (newspaper O Presente and Radio Difusora do Paraná), documents that are part of the Administrative Procedure Min-isterial and bidding processes for the construction of the ecological park. With this study we tried to point out the relationships and links between speculators and the municipality in shap-ing society and the urban design of the city